2012
DOI: 10.1007/s00128-012-0678-8
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Laccase Production and Color Removal by Culturing Fungus Pycnoporus sp. SYBC-L3 in a Textile Wastewater Effluent Supplemented with a Lignocellulosic Waste Phragmites australis

Abstract: We conducted experiments to culture Pycnoporus sp. SYBC-L3 in a medium comprising an industrial waste (dye-containing textile effluent) and a lignocellulosic waste (Phragmites australis) that achieved laccase production while having the color removed from the wastewater. Our experimental results showed that the fungus grew well in liquid submerged cultivation with the diluted textile effluent as the sole culture medium, but relatively low extracellular laccase activity (1.8 U/mL) was produced. Addition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Pycnoporus sp. SYBC-L3 is a robust laccase producer in a nutrition-limited medium19 or an optimized medium at bench or reactor scale20. T. versicolor SYBC-L19 is a newly isolated fungus with great potential in laccase production using water hyacinth as culture substrate21.…”
Section: Methodsmentioning
confidence: 99%
“…Pycnoporus sp. SYBC-L3 is a robust laccase producer in a nutrition-limited medium19 or an optimized medium at bench or reactor scale20. T. versicolor SYBC-L19 is a newly isolated fungus with great potential in laccase production using water hyacinth as culture substrate21.…”
Section: Methodsmentioning
confidence: 99%
“…According to Tychanowicz, Zilly, de Souza, Peralta [34] , structurally different dyes were decolorized because of the high level of laccase generated in response to the presence of soluble phenolic compounds in the glucose/ammonium tartrate–corncob solid-state medium. The fungi produced laccase and removed color at the same time with the supplementation of lignocellulose, providing an alternative approach to deal with textile wastewater and increasing the economic value added by producing laccase [9] . The underlying promoting mechanism should be uncovered to provide a theoretical guideline with strong feasibility in depleting diverse dyes or pollutants.…”
Section: Resultsmentioning
confidence: 99%
“…Stains were found to fade out more rapidly in WRF cultures with low-cost lignocellulose substrates, comprising a wide variety of wastes from agricultural, forest, and food industries. Lignin-degrading enzymes were generally observed to be induced by natural additives than by synthetic media [9] [13] . However, the mechanism behind the simultaneous increase in decolorization and enzyme production in natural substrates has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…SYBC-L3) with potential to remove color from dyecontaining effluent (Liu et al, 2012), and found it secreted extracellular laccase in large amounts, as high as 40,000 U/L in 250 mL Erlenmeyer flasks using a partially optimized medium. Later, the similar productivity of laccase was achieved in 3-L stirred reactor, indicating its potential in larger scale production.…”
Section: Discussionmentioning
confidence: 99%
“…SYBC-L3 (18S rRNA sequence was deposited in GenBank with accession number GU182936) was used in this study for laccase production in air-lift reactor. The strain was identified in our previous study as an effective laccase producer with simultaneous decolorization (Liu et al, 2012), and its culture stock was stored at The Key Laboratory of Industrial Biotechnology, Ministry of Education, School of Biotechnology, Jiangnan University, (Wuxi, China). The fungus was maintained on potato dextrose agar (PDA) slants at 4 C and subcultured on plates at intervals of every two weeks.…”
Section: Fungus Culture Conditions and Laccase Productionmentioning
confidence: 99%